Drivers of Green Supply Chain Initiatives on the Economic Performance of SMEs In Malang - Surachman, Surachman; Aisjah, Siti; Prabandari, Sri Palupi (Jurnal Bisnis dan Manajemen, 2024)
Green Supply Chain Management (GSCM) is a strategic concept of sustainable enterprise development that emerged from the "traditional" concept. GSCM is a way to integrate an environmental perspective into all aspects of supply chain management, including product design, raw material selection, manufacturing processes, final product delivery to consumers, and end-of-life product management. This study aims to examine the driving factors of green supply chain initiatives on the economic performance of MSEs in East Java. This study uses a quantitative approach; the method used is factor analysis using confirmatory factor analysis (CFA). The results showed that of the 40 items scattered, we were able to form six factors that were adjusted to the similarity of the item indicators. The total contribution of the six factors formed is 68.955%, meaning that overall, the six factors formed can answer 68.955% of the research problem. The six factors that drive supply chain initiatives and the economic performance of East Java MSEs include green purchasing, eco-design, internal environmental management, customer cooperation, technological factors, and investment recovery.